Obraz kultury i projekt Asymilacji rdzennej ludności Chile zaprezentowane przez Ignacego Domeykę w książce pt. Araukania i jej mieszkańcy .......... 149 - Pradelle, Maja (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
THE IMAGE OF CULTURE AND THE ASSIMILATION PROJECT OF CHILE’S INDIGENOUS PEOPLE PRESENTED BY IGNACY DOMEYKO IN HIS BOOK ENTITLED: ARAUKANIA I JEJ MIESZKAŃCYIgnacy Domeyko – a Pole from Lithuania, member of the Philomath society, November insurrectionist and emigrant – lived and worked in Chile for almost fifty years. Chileans often refer to him as the father of mining education and, more generally, as a Polish scientist. He is primarily recognized as a geologist and mineralogist, as well as a reformer and rector of the University of Chile. Though his contributions to mining and education are widely acknowledged, his achievements in social and cultural realms are less frequently mentioned. Many are unaware that Domeyko was involved in a project to colonise the southern regions of Chile. He authored a report titled Araucania y sus habitantes, in which he detailed the conditions and lifestyles of Chile’s indigenous Mapuche population within the context of a plan to unify Chilean territory and accommodate regions traditionally inhabited by indigenous people. In his report, Domeyko not only included observations from his travels and natural history but also provided an ethnographic description of Mapuche culture, which he encountered during his trip to southern Chile in 1845. Furthermore, he proposed a concept for the peaceful assimilation and integration of the Mapuche into Chilean society.